The information potential of archival sources on military affairs in Lviv second half of the XIV–XVIII centuries - Bilushchak, Тetiana (Видавництво Львівської політехніки, 2016)
The peculiarities of using of the informative potential of the information potential of archival sources on military affairs in Lviv second half of the XIV–XVIII centuries.
Keywords: information potential; archival sources; Lviv; Magistrate Chancellery; Royal Chancellery; grodskij courts; defense of the city